1999
DOI: 10.1017/s1368980099000610
|View full text |Cite
|
Sign up to set email alerts
|

Health and Nutrition Education in Elementary Schools: Changes in health knowledge, nutrient intakes and physical activity over a six year period

Abstract: Objective: To examine the effects of a health and nutrition intervention, implemented in primary schools of Crete, on health knowledge, nutrient intakes and physical activity of the intervention population. Methods: The intervention group consisted of 24 schools while the control group consisted of 16 schools. The overall duration of the intervention was six years, while the topics of the intervention primarily focused on children' dietary habits, physical activity and fitness. Results: After the completion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 17 publications
(18 reference statements)
0
44
1
8
Order By: Relevance
“…(b) Dietary recalls and history methods Most of the surveys conducted in Greece, with the exception of the survey by Manios and Kafatos (Manios & Kafatos, 1999) and the two conducted on Crete children (Aravanis et al, 1988), were performed retrospectively. The need to validate locally these survey techniques and the inappropriateness of extrapolating food compositional data from elsewhere, such as, for example the USA, to rural Greece or Crete was recognised by national experts.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Dietary recalls and history methods Most of the surveys conducted in Greece, with the exception of the survey by Manios and Kafatos (Manios & Kafatos, 1999) and the two conducted on Crete children (Aravanis et al, 1988), were performed retrospectively. The need to validate locally these survey techniques and the inappropriateness of extrapolating food compositional data from elsewhere, such as, for example the USA, to rural Greece or Crete was recognised by national experts.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The need to validate locally these survey techniques and the inappropriateness of extrapolating food compositional data from elsewhere, such as, for example the USA, to rural Greece or Crete was recognised by national experts. In 1990 a regionally specific validation was conducted in the context of the EPIC study (Katsouyanni et al, 1997), and the self-adminis- (1988) 2 day weighed survey USDA, 'adapted' Crete, rural school children, males Roma-Giannikou et al (1997) 3 day dietary record in household measures German (1986) þ recipes of Greek foods First national survey, school children Manios and Kafatos (1999) 3 day weighed survey Unspecified Crete, primary school children Kafatos (unpublished data) 24 h recall Cretan database with 500 food (USDA 'adapted' þ chemical analyses)…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Twelve of these studies had positive effects on students' health-related fitness knowledge, six studies had a positive effect on students' physical activity levels, and five studies significantly influenced students' fitness levels. Seven of these 12 studies revealed intervention effects both on health-related fitness knowledge and on physical activity (four studies: Harrell et al, 1996;Killen et al, 1989;Manios & Kafatos, 1999;Marcus, Channing Wheeler, Cullen, & Crane, 1987) or fitness levels (three studies: Bush, Zuckerman, Taggart, et al, 1989;Fardy, White, Haltiwanger-Schmitz, & Magel, 1996;Perry et al, 2002). Finally, the results concerning the one study by Caballero et al (2003) with a high methodological quality are unclear because on the one hand, positive effects on students' physical activity were revealed from the data assessed by questionnaire and on the other hand, no intervention effects were shown from the data assessed by a physical activity motion sensor.…”
Section: Y Demetriou Et Al / Educational Research Review 16 (2015) mentioning
confidence: 99%
“…A random sample of 1,046 children was selected to evaluate the effectiveness of the intervention that aimed at promoting healthy dietary and lifestyle habits [20] . The cohort was reassessed during [2001][2002].…”
Section: Subjectsmentioning
confidence: 99%